Les cueillettes commerciales au Québec : capter la diversité socio-environnementale - Sabrina Doyon (EchoGéo)
Commercial wild plant picking is an increasingly popular activity in Québec. While those products are now better known, the activity and the pickers themselves are not. Who are they? How do they get access to the natural resources? Which challenges are they facing? This paper tackles these questions exploring the various practices put forward by pickers. Tsing’s concepts of “salvage accumulation” and “pericapitalist spaces” guide this study, which analyzes the development of picking activities in Québec and presents some of the pickers main characteristics, their local knowledge, practices, territories, and work organization.